A doença de Chagas: repercussões de uma descoberta científica brasileira em Portugal, 1909-1924 - Ewerton Luiz Figueiredo Moura da Silva (Ler História, 2022)
Currently, Chagas disease, or human American trypanosomiasis, affects around 900 people in Portugal, mostly Brazilian immigrants, the main foreign population residing in the country. This article presents a historical inquiry on the first receptions of the Brazilian discovery of Chagas disease in Portugal, a country that had scientists interested in the study of tropical diseases, namely sleeping sickness, or African trypanosomiasis, which affected epidemic in the African colonies of Angola and the island of Príncipe. The time frame of this study is limited between 1909, the date of Carlos Chagas' scientific discovery, and 1924, the year in which the already internationally renowed Brazilian physician, then traveling through Europe, was invited by Portuguese colleagues to give a lecture on American trypanosomiasis in Lisbon. In methodological terms, this article was written based on the work of scrutinizing publications in scientific periodicals, inaugural theses defended in medical schools and Portuguese press news.